1996
DOI: 10.1080/02791072.1996.10471712
|View full text |Cite
|
Sign up to set email alerts
|

Options for Recovery: Promoting Success among Women Mandated to Treatment

Abstract: In recent years imprisonment has been used increasingly for a wide range of nonviolent and petty offenses committed by women. Among incarcerated women, particularly those who are pregnant or parenting, substance use and its deleterious consequences are often exacerbated by imprisonment. Women who have been identified as chemically dependent are also at high risk for losing custody of their children. In California, the Options for Recovery (OFR) treatment program provided an alternative to incarceration or reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The scarce research results that have been reported suggest high levels (48% within 6 months) of noncompliance with court-ordered substance abuse or mental health treatment among randomly selected child neglect cases in a large urban southeastern U.S. county (10). Yet rates of treatment completion were higher for mandated than for voluntary admissions in a California program for women offered treatment as an alternative to incarceration or loss of custody (43). The present study is able to extend this research to outcomes of CPS-pressured treatment for MA users.…”
Section: Introductionmentioning
confidence: 79%
“…The scarce research results that have been reported suggest high levels (48% within 6 months) of noncompliance with court-ordered substance abuse or mental health treatment among randomly selected child neglect cases in a large urban southeastern U.S. county (10). Yet rates of treatment completion were higher for mandated than for voluntary admissions in a California program for women offered treatment as an alternative to incarceration or loss of custody (43). The present study is able to extend this research to outcomes of CPS-pressured treatment for MA users.…”
Section: Introductionmentioning
confidence: 79%
“…There has been much debate and speculation about the merits and limitations of coerced treatment for substance user offenders. Numerous studies have concluded that legal pressure represents a strong and effective external motivator in terms of treatment entry, retention, and outcomes (Berkowitz et al, 1996;Collins and Allison, 1983;Peters, Haas, and Hunt, 2001;Pompi and Resnick, 1987;Watson et al, 1988). However, an increasing number of researchers have started to question the value of coercion after examining the research base.…”
Section: The Effectiveness Of Legal Coercion In Drug and Alcohol Usermentioning
confidence: 96%
“…This may occur either as a consequence of diverting the offender for the current offence or by reducing the likelihood of future offending. Evidence suggests that negative outcomes experienced as a result of drug use do not decrease in prison, but rather are exacerbated [7,8]. Neither is imprisonment associated with any major downturn in the level of criminal activity upon release [3,5].…”
Section: Introductionmentioning
confidence: 97%